The Effectiveness of Covid-19 Health Posters Using Symbols of Indonesian Traditional Fairy Tales on Knowledge, Attitude, and Behaviour - Farhaiza - Ramadhania; Chelomitha Malindra Purnamayanti; Rina Pertiwi; Yunika Tri Yulianti; Susy Katikana Sebayang (Universitas Airlangga, 2022)
Background: The phenomenon of the outbreak of COVID-19 in various parts of the world has created a global panic that has a tremendous effect on all sides of life. Currently, COVID-19 is still a pandemic in Indonesia. Health appeals and messages circulating to prevent the transmission of COVID-19 have not been fully heeded by the public. Without a strong cultural basis, the change in behaviour is difficult for the community to accept. The social context highlighting descriptive norms for certain types of behaviour caused the command norms to conflict with the highlighted behaviour and dissonance (discomfort) increases. Health messages are designed based on symbols that in Indonesian society may be more effective. Objective: This study aims to determine the effectiveness of using traditional Indonesian fairy tale symbols in COVID-19 health posters on knowledge, attitudes, and health behaviours related to COVID-19. Methods: A total of 51 respondents aged 18-40 years who registered on the online questionnaire filled a link with the determination of the sample, namely random sampling which measured knowledge, attitudes, and behaviour before and after being given a poster designed using symbols found in traditional fairy tales. This study uses an online pre-test and post-test. Respondents come from various regions in Indonesia. Results: Respondents stated that posters with fairy tale symbols were interesting, not monotonous, and educative. After seeing posters designed using symbols from traditional fairy tales, respondents' knowledge about COVID-19 increased by 102%, attitudes increased by 6%, and behaviour increased by 17%. Conclusion: The use of symbols in traditional fairy tales conveyed through poster media is effectively used to convey health messages to the public during the COVID-19 period. Health messages should be designed using symbols rooted in people's culture such as traditional Indonesian fairy tales.